Association between body mass index and pathologic complete response in different breast cancer molecular subtypes - Vaca-Cartagena, Bryan; Becerril Gaitan, Andrea; Ferrigno, Ana Sofia; Aranda-Gutierrez, Alejandro; Gonzalez-Mondellini, Fabio A.; Roman-Zamudio, Mariana; Acosta-Sandoval, Marcos A; Torres-Leal, Ma. Inés; Díaz-Pérez, Héctor Marcelino; Cardona-Huerta, Servando; Villarreal-Garza, Cynthia (Journal of clinical oncology, 2021)
e12624Background: Obesity (BMI ≥30 kg/m2) and breast cancer (BC) are two major public health concerns worldwide. Obesity has been linked with aggressive clinicopathological features and inferior survival rates in patients with BC, regardless of molecular subtype. In addition, obesity has been associated with decreased pathological complete response (pCR) rates in some BC cohorts. However, the impact of obesity on pCR rates in different BC molecular subtypes is still a subject of debate. This study aims to explore the impact of obesity on pCR rates in women with different BC subtypes in a public health-care center. Methods: Medical records of women diagnosed with primary BC between 2009 and 2020 in a center in Monterrey, Mexico were reviewed. Patients with stage II or III at diagnosis treated with neoadjuvant chemotherapy (NAC) were considered eligible. Associations between variables were examined using Fisher's exact test of independence, employing logistic regression to calculate odds ratios (OR) when appropriate. Results: A total of 559 patients with a median age at diagnosis of 48 years (range 25-85) were included. Patients were diagnosed with stages II (37%) and III (63%). The most common molecular subtype was HR+/HER2- (49%), followed by TNBC (25%), HR-/HER2+ (15%), and HR+/HER2+ (11%). Regarding BMI, a significant proportion of patients was either overweight (34%) or obese (47%). In this cohort, a total of 134 (24%) patients achieved pCR following NAC with anthracycline- and/or taxane-containing regimens. pCR rates by subtype were as follows: HR-/HER2+ (41%), TNBC (34%), HR+/HER2+ (31%), and HR+/HER2- (13%). A significant association between pCR rates and molecular subtype was found (p<0.001). Overall, obesity was not significantly associated with pCR rates. However, on a stratified analysis, obese patients with HR+/HER2+ tumors had significantly decreased pCR rates compared to their non-obese counterparts (OR=0.21; 95%CI 0.05-0.93; p=0.040). pCR rates according to molecular subtype and obesity status are shown in the table below. Conclusions: Obesity has an adverse influence on pCR rates in patients with HR+/HER2+ tumors. Given the endemic nature of obesity in several low- and middle-income countries, effective programs that focus on prevention, weight reduction strategies, and health promotion are warranted. Furthermore, women should be encouraged to improve their diet and engage in regular physical activity. Efforts to elucidate potential factors that underlie lower pCR rates in obese patients with certain BC subtypes are required. pCR rates according to BMI group and BC subtype, adjusted for stage and grade.SubtypeBMI (kg/m2)pCR (%)OR 95%CIp valueAll subtypes≥30 v <3022 v 250.77 (0.50 - 1.18)0.230HR+/HER2-≥30 v <3013 v 121 (0.45 - 2.21)>0.99HR+/HER2+≥30 v <3016 v 420.21 (0.05 - 0.93)0.040HR-/HER2+≥30 v <3043 v 400.83 (0.31 - 2.22)0.709TNBC≥30 v <3031 v 360.70 (0.29 - 1.64)0.406